Panjang stek dan Rootone-F pada pertumbuhan dan stek pucuk tanaman krisan (Chrysanthemum, sp) - Alfuji Altayani; I Nengah Suaria; I Gusti Made Arjana (Fakultas Pertanian, Universitas Warmadewa, 2018)
This study aims to determine the interaction of Rootone-F concentration and Long Cuttings on chrysanthemum shoot cuttings. This research was conducted in Green House in Agro Pudak Lestari, Pancasari Village, Sukasada District, Buleleng Regency. The time in this study was held for 21 days, from 2, April 2018 to 22, April 2018. This experiment was a factorial experiment using a randomized block design (RBD) pattern. The first treatment of Rootone-F (R) concentration consists of four levels, namely Control: (R0), a concentration of 225 mg.l-1: (R1), a concentration of 450 mg.l-1: (R2), a concentration of 675 mg.l-1: (R3). The second treatment is the length of cuttings consisting of three levels, namely the length of cuttings 4 cm: P1, the length of cuttings 7 cm: P2, the length of cuttings 10 cm: P3. The results of the study show that the interaction between Rootone-F with Long Cuttings has no significant effect (Pâ‰¥0.05) on all observed variables. The treatment of Rootone-F concentration had a very significant effect (P